2016
DOI: 10.2174/1381612822666160203144114
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Acetylcholine Nicotinic Receptors as New Targets for Lung Cancer Treatment

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Smoking accounts for approximately 70% of the cases of non- small cell lung cancer (NSCLC) and 90% of the cases of small-cell lung cancer (SCLC), although some patients develop lung cancer without a history of smoking. Nicotine is the most active addictive component of tobacco smoke. It does not initiate tumorigenesis in humans and rodents, but it alters the pathophysiology of lung cells by inducing the secretion of growth factors, neurotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Genome wide association studies have indicated that α5‐containing nAChRs are closely associated with the risk of lung cancer (Mucchietto et al ., ), but the underlying mechanisms are not yet well known. The published data are contradictory; Krais et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome wide association studies have indicated that α5‐containing nAChRs are closely associated with the risk of lung cancer (Mucchietto et al ., ), but the underlying mechanisms are not yet well known. The published data are contradictory; Krais et al .…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke contains many classes of carcinogens (Hecht and Hoffmann, ) and although nicotine (the addictive and most active component of tobacco smoke) is unable to initiate tumourigenesis in humans and rodents, it promotes tumour growth and metastases by inducing cell‐cycle progression, cell migration and invasion, angiogenesis and the evasion of apoptosis in a variety of tumour cells (reviewed in Egleton et al, ; Schaal and Chellappan, ; Grando, ; Mucchietto et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A large repertoire of nAChR subunits is present in bronchial cells and in the airway epithelium, α7 nAChRs participate in the control of the airway ion transport processes (Maouche et al, ). Various studies have also shown the involvement of nAChRs in the development and progression of lung tumours (see Schaal and Chellappan, ; Mucchietto et al, ). Linkage analyses, and candidate gene and genome‐wide association studies, have shown that variants in the human α3, α5, β4 and α9 nAChR subunit genes are associated with the risk of nicotine dependence, smoking, and lung cancer (see Improgo et al, ; Chikova et al, ).…”
Section: Structure Of Nachrsmentioning
confidence: 99%
“…Neuronal nicotinic ACh receptors (nAChRs) are a family of ACh‐gated cation channels that are ubiquitously expressed in virtually all neurons, where they contribute to many physiological processes in the central and peripheral nervous systems (Albuquerque et al, ; Hurst et al, ). They are also expressed in some non‐neuronal cell types where their physiological role is still being investigated (Grando, ; Mucchietto et al, ). In the brain, nAChRs are expressed at presynaptic sites (where they modulate the release of many different neurotransmitters), at postsynaptic sites (where they influence excitability), and extrasynaptically, where they participate in non‐synaptic communication (Albuquerque et al, ).…”
Section: Introductionmentioning
confidence: 99%